Improved Separation of Odor Responses in Granule Cells of the Olfactory Bulb During Odor Discrimination Learning - Wang, Dejuan; Chen, Yang; Chen, Yiling; Li, Xiaowen; Liu, Penglai; Yin, Zhaoyang; Li, Anan (Frontiers in Cellular Neuroscience, 2020)
In the olfactory bulb, olfactory information is translated into ensemble representations by mitral/tufted cells, and these representations change dynamically in a context-dependent manner. In particular, odor representations in mitral/tufted cells display pattern separation during odor discrimination learning. Although granule cells provide major inhibitory input to mitral/tufted cells and play an important role in pattern separation and olfactory learning, the dynamics of ensemble representation in granule cells during odor discrimination learning remain largely unknown. Here, we studied odor representation in granule cells of the olfactory bulb using fiber photometry recordings in awake behaving mice. We found that odors evoked reliable, excitatory responses in the granule cell population. Intriguingly, during odor discrimination learning, odor representation in granule cells exhibited improved separation and contained information about odor value. In conclusion, we show that granule cells in the olfactory bulb display learning-related plasticity, suggesting that they may mediate pattern separation in mitral/tufted cells.